Developing Leadership Qualities in Practice Teachers - FADEL, Mohamed Rafik (Journal of Human Sciences, 2011)
One of the most important characteristics in being a goodteacher is being a good leader. It is said that good leaders aremade not born and so should be good teachers; they should bemade not born. In the field of teachers’ training in Algeria,practice teachers who supervise student teachers during theirpractice at schools are generally selected among the mostexperienced teachers who are also judged to be the mostcompetent. Their role is to provide guidance to the trainees andto take charge of and evaluate them in their teaching practice.However, these practice teachers have never been prepared totake upon themselves the role of guide or leader to other teachersor trainees.Through this article, we want to highlight the characteristics of agood practice teacher and the role of leader he/she must play inorder to be an effective element during the training period.Likewise, using Blake and Mouton Managerial Grid, we showwhat leadership style our practice teachers represent whenmentoring student teachers and suggest how these qualities canbe brought to the best levels of achievement.